EVALUASI PENYIMPANAN DAN DISTRIBUSI OBAT DI INSTALASI FARMASI DAN PERBEKALAN KESEHATAN KABUPATEN BONE BOLANGO TAHUN 2010 DAN 2011 - , vyani kamba, Prof. Dr. Dra. Sri Suryawati,Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Pharmacy and Medical Supplies Unit of Bone Bolango regency is a technical unit area that has task of managing medicines and medical supplies from a variety of sources. Found a lot of drugs and medical supplies are damaged or expired. In 2007 destroyed drugs and medical supplies valued Rp. 97,612,644., and at 2010 amounting to Rp. 147,424,895., Research then should be conducted regarding the distribution and storage of medicines in Pharmacy and Medical Supplies Unit of Bone Bolango regency. Method: The research uses Case Study design with qualitative and quantitative data. Quantitative data obtained by observation retrospective document and concurrent. Qualitative data obtained from in-depth interviews. Results: The results of research showed in Pharmacy and medical supplies Unit of Bone Bolango regency : the amount of drug that fits actual and recorded inventory was 91%, medicines stored by FEFO system was 94.5%, and by FIFO system was 5.5%. Quantity of damaged/expired drug at 2010 was 23.8% and at 2011 was 18%. Percentage value of damaged/expire drug at 2010 was 9.3% and 6% in 2011. Average stock position at 2010 was 28 months and at 2011 was 22 months, Percentage of health facilities submitting requisitions on time at 2010 was 84% and at 2011 was 82%. Warehouse lead time at 2010 was 2.74 days and 2.12 days at 2011. Percentage number of item supplied out of total requested by client at 2010 was 79% and 68% at 2011. Conclusion: The process of storage must be repaired because found drugs that do not fit between actual and recorded inventory, drugs was damaged or expired, average stock position more than 18 months and less then 6 months. Distribution process need to be addressed because found warehouse leaf item supplied out of total requested by client.